Effect of Pursed Lips Breathing Exercise on Respiration Rate in Children with Bronchopneumonia at Sumber Sanas Hospital - Hamidah, Dwi Salsa (Jurnal Kesehatan STIKes Sumber Waras, 2026)
Bronchopneumonia, also referred to as lobular pneumonia, is an inflammatory condition of the lung parenchyma that may extend to the bronchioles and alveoli. Its etiology includes bacteria, viruses, fungi, and foreign bodies. One of the non-pharmacological interventions that can be applied is pursed lips breathing (PLB), which is beneficial for improving ventilation, releasing trapped air, slowing the respiratory rate, and promoting relaxation in children. This study aimed to examine the effect of PLB exercise on the respiratory rate of children with bronchopneumonia at Sumber Waras Hospital in 2025. A quantitative method was employed with a quasi- experimental one-group pretest–posttest design. The study sample consisted of 10 children with bronchopneumonia, selected using a total sampling technique. Data were analyzed with a dependent t-test to compare respiratory rate values before and after the intervention. The findings revealed a reduction in the average respiratory rate following PLB exercise. Statistical analysis confirmed a significant difference in respiratory rate between pre- and post-intervention (p = 0.000). Conclusion: Pursed lips breathing exercise is effective in lowering respiratory rate among children with bronchopneumonia. This intervention can be recommended as a supportive non-pharmacological therapy in pediatric nursing care for respiratory problems.